Low atypical lymphocyte score as a predictor of non-severe dengue - Chandramathi Samudi Raju; Mari Kono; Kah Wai Looi; Jin Xu Ong; Chin Aun Tan; Chong Siang Ang; Peter Hao Yuan Tan; Hemalatha Shamnugam; Shamala Devi K. C. Sekaran; Sharifah Faridah Syed Omar; Lucy Chai See Lum (BMC Infectious Diseases)
Abstract Background Severe dengue has been linked to the presence of atypical lymphocytes, which can be quantified using the Q-flag parameter on a hematology analyzer. A higher atypical lymphocyte count has previously been associated with severe dengue. We aimed to evaluate the feasibility of the atypical lymphocyte score to provide an early prognosis for dengue severity. Method A prospective observational study enrolled adult patients admitted to the Infectious Disease ward with a febrile illness of less than 7 days. Blood samples obtained daily until discharge, were processed with XN-20 hematology analyzer with specific attention given to atypical lymphocyte score. Severe dengue cases were classified according to the 2009 World Health Organization Classification. Results A total of 287 cases of laboratory-confirmed dengue, including 25 severe cases, were included. Dengue fever compared to non-dengue patients manifested increased lymphocytes within the high fluorescent zone on Day 6, The atypical lymphocyte score (ALS) of severe dengue showed an early rise, reaching a saturation point of 300 and remaining stable within the timeframe of days 4 to 8 post-fever onset. All but one severe dengue patient had a score exceeding 100 on day 4 post fever onset. Conclusion An atypical lymphocyte score below 100 on day 4 post fever onset, may serve as a predictive indicator that severe dengue is less likely to develop, potentially allowing for a lower level of medical intervention. These findings may contribute to more efficient resource allocation during outbreaks. Trial registration The study was registered under National Medical Research Registration of Malaysia, (NMRR-18–3347-45473, 1 Sept 2019).